Suara Kebebasan Dalam Cerita Pendek Kafanu Al - Ustazi Karya Haifa Bitar: Kajian Ginokritik Elaine Showalter - Nizar, Mohammad; Dewi Asih, Kusuma (Philosophiamundi, 2023)
This article attempts to express feminist literary criticism of the writer Haifa Bitar in one of his works, in the short story anthology "Gurubun wa Kitabah" with the title "Kafanu Al - Ustazi" using the gynocritical study initiated by Elaine Showalter. Giniocriticism itself is a theory of feminist literary criticism which discusses women as writers (women play the role of writers or writers). Divides four models in this study, namely first, female writers and female biology. Second, female writers and female psychology. Third, women writers and women's psychology, and fourth, women writers and women's culture. Of the four models, in this article the researcher will focus on discussing women writers and women's psychology as well as women writers and women's culture. Meanwhile, the research method in this research uses a qualitative approach with descriptive-analytic methods. The descriptive-analytic method is research that aims to describe, analyze and interpret data, in this case the data produced by female writers and female psychologists, differentiated based on Sigmund Freud's psychological structure in the form of: Id, Ego and Superego. Meanwhile, female writers and female culture are found in terms of values, institutions, relationships and communication methods. Based on these data, it shows that the author, Haifa Bitar, has the courage to reveal the injustice of women whose rights are oppressed, especially in the realm of education and he wants to fight the patriarchal culture which seems to be ingrained in himself and the word "woman" itself, especially in the 'Eastern' world.